Rancang Bangun Aplikasi Penggajian Menggunakan Hybrid Mobile Programming di CV Agung Glass - Rohmat Taufiq; Dian Kasoni; Catur Siswoko; Liesnaningsih Liesnaningsih (Jurnal Informatika Universitas Pamulang, 2020)
Salary is remuneration received by workers in the form of money based on a certain time. Processing employee salary data is very important for companies to appreciate their employees who are already working. The payroll process for employees at CV Agung Glass currently uses Ms. Excel, this causes several errors that often occur in the salary calculation process. As a growing company, CV Agung Glass needs a data processing application that can assist in processing employee payroll data quickly, precisely, and thoroughly. The method used in this payroll system is the iteration method, which is an application design method by sequencing the steps in designing the application, then repeating it if there are errors or developments for the application. The programming language used to make this payroll application is hybrid programming for mobile by combining two different programming languages, namely mobile programming using Android Studio and web programming using PHP.